A hybridized IT2FS-DEMATEL-AHP-TOPSIS multicriteria decision making approach: Case study of selection and evaluation of criteria for determination of air traffic control radar position - Petrovic, Ivan; Kankaras, Milan (Decision Making: Applications in Management and Engineering, 2020)
In this paper the criteria for selection of air traffic control (ATC) radar position that provide successfully fulfilled role of radar in air traffic management are determined and evaluated. Using the questionnaire, experts determined the initial criteria for selecting the radar position. Furthermore, the hybridized DEMATEL-AHP-TOPSIS model was modified by using the interval type-2 fuzzy sets (IT2FS). Less important criteria were eliminated by using the IT2FS-DEMATEL method, the prioritization of the final criteria was carried out by using the IT2FS-AHP method and a multi-criteria decision making model was proposed. Of the four ATC radar positions offered, the optimal position was selected by using the IT2FS-TOPSIS method. Validation of model was carried out by using Fuzzy and the IT2FS modified methods: TOPSIS, COPRAS and MABAC. A sensitivity analysis was carried out through 36 scenarios of changes in the criteria’s weights.